Scheduling of training and recovery during the in-season weekly micro-cycle: Insights from team sport practitioners - Cross, R.; Siegler, J.; Marshall, P.; Lovel, R. (European Journal of Sport Science, 2019)
The aim of this study was to determine the in-season micro-cycle scheduling strategies used in professional team sport with particular reference to the reasoning and perceptions that underpin current practice. An online survey was completed by 35 practitioners from professional collision (C; Australian rules football: n = 9; rugby league: n = 6; rugby union: n = 2) and non-collision (NC; soccer; n = 18) sports. Respondents identified a common 48 h post-match recovery period, with few scheduling training stimuli during this period (NC: range: 0-17%; C: range: 0-47%). The majority (C: 78%; NC: 89%) of resistance training sessions were concurrent in nature, often delivering resistance training in the afternoon following field-based training (C: 72%; NC: 92%). NC practitioners were less satisfied with the maintenance of strength, power and hypertrophy (33-44%) versus C sports (59-76%), reflected by the lower frequency of prescription reported (C: 2.4 ± 0.6; NC: 1.5 ± 0.9; p = .003). Cold water immersion following both matches and daily training was highly prevalent, as was the adoption of self-report tools to monitor recovery. The congested and concurrent nature of training prescription during the micro-cycle, together with the universal adoption of routine cold water immersion warrants further investigation to inform evidence-based prescription and scheduling of training and recovery modalities in professional team sports.